2008
DOI: 10.1111/j.1525-1594.2008.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Better Sleep Quality and Less Daytime Symptoms in Patients on Evening Hemodialysis: A Questionnaire‐based Study

Abstract: The aims of this study were to investigate the prevalence of sleep disorders in patients with end-stage renal disease (ESRD), and to assess the effect of dialysis schedule on sleep quality and the presence of daytime symptoms. We prospectively selected 150 long-term hemodialysis (HD) patients in three groups (morning, afternoon, and evening dialysis) and gave them a sleep questionnaire, the Epworth sleepiness scale and the Pittsburgh sleep quality index. Snoring was the most common complaint (56%), followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The diurnal rhythm of melatonin is disturbed in patients with ESRD, and it is also related to the degree of kidney dysfunction in patients with chronic kidney disease (CKD) [69] Some studies have suggested that the timing of the dialysis shift alters the severity of insomnia, such that insomnia is worse among patients who are dialyzed in the morning [70,71], but this has not been shown in all studies [72]. Lugaresi et al declared that Snoring would affect 19% to 37% of the CKD population and more than 50% of ESRD [73]. In our work 20(50%) of CKD were snorers, There were highly significant differences P < 0.001 in the prevalence of reported snoring, among HD compared with the conservative group.…”
Section: Discussionmentioning
confidence: 98%
“…The diurnal rhythm of melatonin is disturbed in patients with ESRD, and it is also related to the degree of kidney dysfunction in patients with chronic kidney disease (CKD) [69] Some studies have suggested that the timing of the dialysis shift alters the severity of insomnia, such that insomnia is worse among patients who are dialyzed in the morning [70,71], but this has not been shown in all studies [72]. Lugaresi et al declared that Snoring would affect 19% to 37% of the CKD population and more than 50% of ESRD [73]. In our work 20(50%) of CKD were snorers, There were highly significant differences P < 0.001 in the prevalence of reported snoring, among HD compared with the conservative group.…”
Section: Discussionmentioning
confidence: 98%
“…However, young and employed patients with evening dialysis sessions were found to have higher sleep quality (25). In another research, Hsu et al (2008) claimed that sleep quality significantly improved in patients receiving evening dialysis, and sleep apnea was reported as the most frequent sleep disorder in these patients (26). Sleep quality is influenced by several factors including lifestyle, physical problems and psychological disorders, such as depression and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, review of literature revealed conflicting results regarding the relationship between sleep quality and timing of dialysis. Accordingly, some studies have reported poor sleep quality in patients undergoing dialysis during the day, whereas patients with evening dialysis shifts had higher sleep quality (25,26). Also, a number of studies have suggested that patients with morning dialysis shifts tend to have higher sleep quality (27).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with CKD usually have EDS which is always considered as distressing as nocturnal symptoms and have an impact on quality of life Shayamsunder et al, 2005). In our previous report, we emphasized not only nocturnal sleep quality but also EDS which make difference in CKD patients under different dialysis schedule (Hsu et al, 2008). Thus our animal model of CKD is more helpful than clinical studies to clarify this issue.…”
Section: Ckd Ratsmentioning
confidence: 92%
“…The mortality of CKD patients also follows a circadian variation with increased rate of death in the morning (Tisler et al, 2008). We have shown that CKD patients under regular evening hemodialysis had better sleep quality and less daytime sleepiness compared with those under morning and afternoon shifts (Hsu et al, 2008). The nocturnal endogenous melatonin rhythm decreases with advanced CKD (Koch et al, 2010), and nocturnal hemodialysis partially restores circadian rhythm of melatonin and improves nocturnal sleep in patients with CKD (Koch et al, 2009a(Koch et al, , 2009b.…”
Section: Introductionmentioning
confidence: 97%